THE FREQUENCY OF WOUND INFECTION WITH PARA-UMBILICAL INCISION VERSUS INTRA-UMBILICAL INCISION FOR LAPAROSCOPIC CHOLECYSTECTOMY - HAQ, TU; KHAN, N; TABASUM, T; TABASUM, S; KABIR, T; ULLAH, A (Biological and Clinical Sciences Research Journal, 2024)
The elective laparoscopic cholecystectomy, also known as minimally invasive cholecystectomy is regarded as the treatment of choice for surgical treatment of symptomatic patients with cholecystolithiasis. Objective: To measure the frequency of wound infection when laparoscopic cholecystectomy is performed by Para-Umbilical Incision versus Intra-Umbilical Incision. Methods: This randomized controlled trial was conducted in the Department of General Surgery, Federal Government Services Hospital, Islamabad, over six months. Patients who met the inclusion criteria were identified, and informed consent was obtained from either the patients themselves or their guardians. Demographic information, including name, age, weight (in kilograms), and address, was recorded to facilitate follow-ups, along with a detailed history of pre-existing medical conditions. Results: A total of 200 patients were enrolled in the study, with mean age of the participants in Group A was 42.5 ± 8.3 years, while in Group B, it was 41.8 ± 9.1 years. Group A comprising 45 males and 55 females, and Group B having 50 males and 50 females (p > 0.05). Similarly, the mean BMI was not significantly different between the groups, with 26.4 ± 3.1 kg/m² in Group A and 26.2 ± 3.3 kg/m² in Group B (p > 0.05). The frequency of wound infections was significantly higher in Group A (para-umbilical incision) at 14% compared to Group B (intra-umbilical incision) at 5%. This difference was statistically significant, with a p-value of 0.03, indicating a lower risk of wound infections associated with intra-umbilical incisions. Conclusion: It is concluded that the intra-umbilical incision is associated with a significantly lower frequency of wound infections compared to the para-umbilical incision in laparoscopic cholecystectomy.